Pengembangan Perangkat Pembelajaran Flipped Classroom pada Materi Impuls dan Momentum - Yuni Evi Meliani Sihaloho; Wayan Suana; Agus Suyatna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
This research was intended to produce flipped classroom learning tools on impulse and momentum materials to help overcome insufficient time to get all students to understand the material well, and to know the validation of products by experts and practitioners and to seek out the attractiveness, convenience, and usefulness of the tools. The development model used in this research was the ADDIE model consisting of five phases: analysis, design, development, implementation, and evaluation, which were restricted to the development phase. In the analysis phase, it was done by doing requirement analysis by giving questionnaires to students and interviewing to a teacher in Metro 1 Public HighSchool. At the design phase, it was done by producing learning tools that include syllabus, lesson plans, lessons video, student’s worksheet for video’s companion, and student’s worksheet for classroom learning. At the development phase, it was done by testing the product. The result obtained from the expert validation test was 3.58 of the average product score with the qualification is very valid, the practitioners validation test result was 3.66 of the average score with qualification is very valid, and the result of the 1-1 test is 3.47 of the attractiveness average scores, 3.32 of the convenience average scores, and 3.70 of the usefulness average scores, with qualifications are very attractive, very convenient, and very useful. The conclusion from the results of this development research is the flipped classroom learning tools for impulse and momentum materials are worthy to betested in learning physics.Keywords: ADDIE, Development, Impulse and Momentum, Learning Tools.